Sharing Session sebagai Upaya Mengembangkan Pemahaman Diri melalui Layanan Konseling Kelompok - Husrin Konadi; Syarifah Ainy Rambe (LSM Catimore dan Sahabat, 2023)
Self-understanding is a cognitive representation of adolescents regarding self-concept. Self-understanding is very important, because it involves how a person or student perceives himself positively or negatively, good or bad. Sharing sessions are activities that function as a forum for providing information and education. The purpose of this service is to increase students' understanding in optimizing their activities at school and outside of school. The method used is using the service learning technique. The results of this sharing session showed that students' understanding/knowledge related to the importance of understanding themselves and also seen from the increasing enthusiasm of students to take part in several activities carried out at school.